Myeloid C-Type Lectin Receptors in Tuberculosis and HIV Immunity: Insights Into Co-infection? - Naqvi, Kubra F.; Endsley, Janice J. (Frontiers in Cellular and Infection Microbiology, 2020)
C-type lectin receptors (CLRs) are carbohydrate binding pattern recognition receptors (PRRs) which play a central role in host recognition of pathogenic microorganisms. Signaling through CLRs displayed on antigen presenting cells dictates important innate and adaptive immune responses. Several pathogens have evolved mechanisms to exploit the receptors or signaling pathways of the CLR system to gain entry or propagate in host cells. CLR responses to high priority pathogens such as Mycobacterium tuberculosis (Mtb), HIV, Ebola, and others are described and considered potential avenues for therapeutic intervention. Mtb and HIV are the leading causes of death due to infectious disease and have a synergistic relationship that further promotes aggressive disease in co-infected persons. Immune recognition through CLRs and other PRRs are important determinants of disease outcomes for both TB and HIV. Investigations of CLR responses to Mtb and HIV, to date, have primarily focused on single infection outcomes and do not account for the potential effects of co-infection. This review will focus on CLRs recognition of Mtb and HIV motifs. We will describe their respective roles in protective immunity and immune evasion or exploitation, as well as their potential as genetic determinants of disease susceptibility, and as avenues for development of therapeutic interventions. The potential convergence of CLR-driven responses of the innate and adaptive immune systems in the setting of Mtb and HIV co-infection will further be discussed relevant to disease pathogenesis and development of clinical interventions.